2011
DOI: 10.1097/ico.0b013e3181d25e4d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graft–Host Interface on the Quality of Vision After Deep Anterior Lamellar Keratoplasty in Patients With Keratoconus

Abstract: In selected patients, quality of vision after DALK was comparable to that after PK when stromal excision was extended to the DM and inferior to vision after PK when layers of stroma were left adherent to the DM. Advances in DALK technique are required to allow easier and repeatable baring of the DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…One study of DALK in patients with keratoconus compared visual results of those with a stroma-stroma interface (pre-DM-DALK) against those with a DM-stroma interface (DM-DALK). 37 Low-contrast visual acuity was significantly inferior to PKP in the pre-DM-DALK group, but equivalent to PKP in the DM-DALK group. Pelli-Robson contrast sensitivity was comparable after PKP and DM-DALK, but significantly worse in the pre-DM-DALK group.…”
Section: The Interface In Dalk -What Does It Tell Us About the Interfmentioning
confidence: 81%
See 2 more Smart Citations
“…One study of DALK in patients with keratoconus compared visual results of those with a stroma-stroma interface (pre-DM-DALK) against those with a DM-stroma interface (DM-DALK). 37 Low-contrast visual acuity was significantly inferior to PKP in the pre-DM-DALK group, but equivalent to PKP in the DM-DALK group. Pelli-Robson contrast sensitivity was comparable after PKP and DM-DALK, but significantly worse in the pre-DM-DALK group.…”
Section: The Interface In Dalk -What Does It Tell Us About the Interfmentioning
confidence: 81%
“…Non-significant trends for better high-contrast VA after DM-DALK compared with pre-DM-DALK have been found. 1,37 In a similar study of 236 keratoconic eyes, Sarnicola et al found no difference in highcontrast VA outcomes between DM-DALK and pre-DM-DALK at a mean follow-up of 2.5 years.…”
Section: The Interface In Dalk -What Does It Tell Us About the Interfmentioning
confidence: 94%
See 1 more Smart Citation
“…4,5 Overall success in separating DM from the overlying tissue with this technique has been reported to be approximately 70% to 80% worldwide. 4,5 CXL produces a compaction of collagen fibers that is confined to the anterior 250 µm of the corneal stroma, as has been shown on electrophoresis ex vivo and confocal scanning laser microscopy in vivo.…”
mentioning
confidence: 99%
“…4,5 Overall success in separating DM from the overlying tissue with this technique has been reported to be approximately 70% to 80% worldwide. 4,5 CXL produces a compaction of collagen fibers that is confined to the anterior 250 µm of the corneal stroma, as has been shown on electrophoresis ex vivo and confocal scanning laser microscopy in vivo. [6][7][8][9] Nonetheless, compaction of the anterior stroma could theoretically hinder formation of the "Big Bubble" cleavage plane in the posterior stroma and therefore concerns have been raised about the possibility of performing a successful "Big Bubble" technique in corneas previously treated with CXL.…”
mentioning
confidence: 99%